Prediction of the Candida antarctica Lipase A Protein Structure by Comparative Modeling and Site‐Directed Mutagenesis. - Kasrayan, Alex; Bocola, Marco; Sandstroem, Anders G.; Laven, Gaston; Baeckvall, Jan‐E. (ChemInform, 2007)
Abstract ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 200 leading journals. To access a ChemInform Abstract, please click on HTML or PDF.